Analisis Komparatif Efektivitas Antipiretik antara Bahan Alami dan Sintetik terhadap Penurunan Suhu Tubuh pada Mencit (Mus musculus) - Umniyyah Azizah Al jufri; Surawalia Said; Siti Srihandayani Najib; Aqilah Nurul Izzah; Nurul Indah Lestari; Intan Rusdin; A. Nurfadiyah Izzaty Dwiputri (An-Najat, 2025)
Fever is a physiological response to infection or inflammation, characterized by an increase in body temperature beyond the normal threshold. To reduce fever, antipyretic drugs such as acetaminophen (paracetamol) and nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used. This study aimed to evaluate the antipyretic effectiveness of several drugs by observing their ability to reduce fever in mice induced with pyrexia using peptone solution. The method involved intraperitoneal administration of peptone to induce fever, followed by treatment with different classes of antipyretic agents. Body temperature was measured at regular intervals to assess the degree and duration of temperature reduction. The results are expected to show a comparative profile of each drug’s antipyretic activity and determine which agent is most effective in lowering body temperature. This experiment provides a scientific understanding of the pharmacodynamics of antipyretic drugs and supports evidence-based selection for fever management. The findings also contribute to laboratory-based pharmacological education and reinforce the clinical relevance of antipyretic classification.